Preparation method and application of copper-doped Ni-MOF catalyst
Through the preparation of copper-doped Ni-MOF catalyst, the problem of unsatisfactory oxidation current density in electrochemical ammonia oxidation is solved, the catalytic activity and current density are improved, the starting potential is reduced, and a more efficient ammonia oxidation reaction is achieved.
Patent Information
- Application Number
- CN202411100848.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2024-12-27
AI Technical Summary
The oxidation current density of existing catalysts is not ideal during electrochemical ammonia oxidation, and the ammonia oxidation overpotential is high, making it difficult to effectively overcome these challenges.
Using the preparation method of copper doped Ni-MOF catalyst, copper nitrate, nickel nitrate and terephthalic acid are sonicated in a solvent of N,N-dimethylformamide, anhydrous ethanol and deionized water. Hydrothermal reaction, a gray-blue powder was prepared as a catalyst, and its electronic structure and active specific surface area were regulated to improve catalytic activity.
Through copper doping, the catalytic activity of Ni-MOF in ammonia oxidation is improved, the starting potential is reduced, and the current density is increased, so that it can show higher efficiency and performance in electrochemical ammonia oxidation reaction.
Smart Images

Figure CN119192593A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of electrochemical ammonia oxidation catalysts, and specifically relates to a preparation method and application of a copper-doped Ni-MOF catalyst. Background Art
[0002] In recent years, electrochemical ammonia oxidation reaction (AOR) has attracted much attention in direct ammonia fuel cells and ammonia wastewater treatment. Ammonia (NH3) is an excellent hydrogen storage medium that can effectively solve the hydrogen storage problem. In addition, in ammonia-rich wastewater, ammonia nitrogen is mainly in the form of ionized ammonia (NH4 + -N) and free ammonia (NH3-N). Compared with traditional denitrification technologies, the electrochemical direct ammonia nitrogen oxidation method has higher energy utilization, simpler operation and fewer toxic by-products.
[0003] The electrochemical oxidation of ammonia at the anode is very slow and has a high oxidation overpotential, so it is very important to develop efficient catalysts to overcome these challenges. Pt and Pt-based catalysts are the most active catalytic materials with the lowest ammonia oxidation overpotential so far, and are therefore widely used in the study of electrochemical ammonia oxidation.
[0004] Although non-Pt catalyst Ni(OH)2 exhibits certain catalytic activity, its oxidation current density is not ideal enough. It is expected that this problem can be solved by synthesizing multi-metal catalysts through element doping.
[0005] Metal organic framework (Ni-MOF) is a MOFs material with ultra-large cavities and high specific surface area. It has been widely used in the preparation of photocatalytic water splitting to produce hydrogen (Chinese patent CN11642237A), lubricating materials (Chinese patent CN113897235A) and other fields. Summary of the invention
[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0008] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a copper-doped Ni-MOF catalyst.
[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a copper-doped Ni-MOF catalyst is provided, comprising:
[0010] Copper nitrate, nickel nitrate and terephthalic acid are added into a solvent consisting of N,N-dimethylformamide, anhydrous ethanol and deionized water, and subjected to ultrasonic treatment to obtain a mixed solution.
[0011] The mixed solution was transferred to a polytetrafluoroethylene-lined autoclave and heated for reaction;
[0012] After the reaction is completed, the reactor is cooled to room temperature and taken out. The reactants are centrifuged, washed, and dried to obtain a gray-blue powder, which is the copper-doped Ni-MOF catalyst.
[0013] As a preferred embodiment of the preparation method of the present invention, the volume ratio of N,N-dimethylformamide, anhydrous ethanol and deionized water is 32:2:2;
[0014] The molar ratio of terephthalic acid to the total amount of metal ions is 1-1.5 mmol: 1-1.5 mmol;
[0015] The ratio of the N,N-dimethylformamide to terephthalic acid is 30-32 mL: 1-1.5 mmol.
[0016] As a preferred embodiment of the preparation method of the present invention, the molar ratio of the nickel nitrate to the copper nitrate is 0-1.5:0-1.5.
[0017] As a preferred embodiment of the preparation method of the present invention, the molar ratio of the nickel nitrate to the copper nitrate is 1:0.5.
[0018] As a preferred embodiment of the preparation method of the present invention, the ultrasonic treatment has an ultrasonic time of 20 to 30 minutes and an ultrasonic power of 100 to 200W.
[0019] As a preferred embodiment of the preparation method of the present invention, the heating reaction has a reaction temperature of 140° C. and a reaction time of 10 h.
[0020] As a preferred embodiment of the preparation method of the present invention, the centrifugation further comprises washing the product with anhydrous ethanol and deionized water for 2 to 3 times respectively.
[0021] As a preferred embodiment of the preparation method of the present invention, the drying comprises vacuum drying at a temperature of 60° C. and a drying time of 10 to 12 hours.
[0022] Another object of the present invention is to overcome the deficiencies in the prior art and provide a copper-doped Ni-MOF catalyst and apply it to electrochemical ammonia oxidation.
[0023] Beneficial effects of the present invention:
[0024] (1) The present invention provides a method for preparing a copper-doped Ni-MOF catalyst, which can enhance the conduction effect of electrons in the reaction process, promote the rate of electrochemical ammonia oxidation reaction, and improve its performance; at the same current density, the starting potential of Ni-MOF can be reduced from 0.61 (V vs. Ag / AgCl) to 0.39 (V vs. Ag / AgCl), and the current density at the same voltage can be increased from 14.85 mA / cm 2 Increased to 87.95 mA / cm 2 , which proves that the catalytic activity of Ni-MOF in ammonia oxidation can be improved by copper doping.
[0025] (2) The present invention realizes the hydrothermal method to prepare nickel nitrate and copper nitrate in different proportions. x Cu y -MOF catalyst (where x+y=1.5mmol), by regulating its electronic structure and active specific surface area, is conducive to the electrochemical ammonia oxidation reaction; the preferred molar ratio of nickel nitrate to copper nitrate is 1:0.5, and the maximum current density of the prepared catalyst reaches 87.95mA / cm 2 , the onset potential is as low as 0.39 (V vs.Ag / AgC l), and the catalytic activity is optimal. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0027] Figure 1 Ni1Cu prepared in Example 2 of the present invention and Comparative Example 1 0.5 X-ray diffraction (XRD) patterns of Ni-MOF and Ni-MOF samples.
[0028] Figure 2 The performance comparison diagram of the ammonia oxidation reaction and oxygen evolution reaction of the Ni-Cu-MOF samples prepared in Examples 1 to 5 of the present invention and Comparative Examples 1 to 2 is shown. Figure 2 (a) and (b) are the CV and LSV curves of ammonia oxidation reaction (AOR) in 1M KOH+0.5M NH4Cl electrolyte, respectively; Figure 2 (c) and (d) are the CV and LSV curves of oxygen evolution reaction (OER) in 1M KOH electrolyte, respectively.
[0029] Figure 3The double layer capacitance (Cdl) diagram of the Ni-Cu-MOF samples prepared in Examples 1 to 5 of the present invention and Comparative Examples 1 to 2 in 1M KOH+0.5M NH4Cl electrolyte.
[0030] Figure 4 Ni1Cu prepared in Example 2 of the present invention 0.5 - Steady-state test (it) diagram of MOF samples in 1M KOH and 1M KOH+0.5M NH4Cl electrolytes at a voltage of 0.65 (V vs. Ag / AgCl). DETAILED DESCRIPTION
[0031] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0032] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0033] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0034] The electrochemical ammonia oxidation performance of the present invention is obtained by testing with an electrochemical workstation:
[0035] First, weigh 2.5 mg of catalyst and 2.5 mg of carbon black into a centrifuge tube, add 1 mL of anhydrous ethanol and 50 μL of Nafion solution, mix by ultrasonication to prepare a suspension, and then drop it in small amounts and multiple times to an area of 0.1256 cm 2 The catalyst loading was 0.35 mg / cm 2 working electrode.
[0036] Secondly, electrochemical tests were carried out using a three-electrode electrolytic cell reaction device. A catalyst-loaded glassy carbon electrode was used as the working electrode, an Ag / AgCl electrode (saturated KCl) was used as the reference electrode, and a platinum wire was used as the counter electrode. They were connected to an electrochemical workstation and electrochemical tests were carried out in 1M KOH and 1M KOH+0.5M NH4Cl electrolytes, respectively.
[0037] Before the electrochemical test, the electrolyte was saturated with Ar. The catalyst was activated by cyclic voltammetry (CV) at a scan rate of 50 mV / s with 1 M KOH as the electrolyte in the voltage range of 0 to 0.8 (V vs. Ag / AgCl). Subsequently, 1 M KOH + 0.5 M NH4Cl was used as the electrolyte, the scan rate was changed to 25 mV / s, and the AOR activity curve was obtained by scanning.
[0038] Linear Sweep Voltammetry (LSV) was used to test the onset potential and current response value of ammonia oxidation at a scan rate of 2mV / s.
[0039] The double-layer capacitance (Cdl) was measured by cyclic voltammetry at scan rates of 20, 40, 60, 80, and 100 mV / s, and is proportional to the active specific surface area of the catalyst.
[0040] Steady-state test (IT), steady-state refers to the state in which the electrochemical parameters such as electrode potential, current density, electrode interface state, etc. change little or remain basically unchanged. The catalyst was tested for steady-state at a voltage of 0.65 (Vvs.Ag / AgCl) using chronopotentiometry to obtain a curve of current change over time.
[0041] Example 1
[0042] The molar ratio of nickel nitrate to copper nitrate is 1.25:0.25. 1.25 Cu 0.25 - Preparation and testing of MOF catalysts:
[0043] (1) Weigh 0.362 g nickel nitrate, 0.060 g copper nitrate, and 0.249 g terephthalic acid, add 32 mL N,N-dimethylformamide, 2 mL anhydrous ethanol, and 2 mL deionized water, and mix thoroughly with ultrasonic.
[0044] (2) The mixed solution was transferred to a polytetrafluoroethylene-lined high-pressure reactor and reacted in an oven at 140°C for 10 h.
[0045] (3) After the reaction was completed, the reactor was cooled to room temperature and the obtained precipitate was washed three times by centrifugation with anhydrous ethanol and deionized water respectively.
[0046] (4) Finally, the product was dried in a vacuum oven at 60°C for 12 h. The obtained gray-blue powder was Ni 1.25 Cu 0.25 -MOF.
[0047] After the above catalyst was prepared into a working electrode for electrochemical ammonia oxidation test, see Figure 2 (b), the starting potential is 0.45 (Vvs.Ag / AgCl), and the current density is 41.12 mA / cm at the same voltage 2 .
[0048] Example 2
[0049] Ni1Cu with a molar ratio of nickel nitrate to copper nitrate of 1:0.5 0.5 - Preparation and testing of MOF catalysts:
[0050] The same synthesis method was used as in Example 1, wherein 0.290 g nickel nitrate and 0.120 g copper nitrate were weighed, and other conditions were the same as in Example 1. The final product was named Ni1Cu 0.5 -MOF.
[0051] After the above catalyst was prepared into a working electrode for electrochemical ammonia oxidation test, see Figure 2 (b), the starting potential is 0.39 (Vvs.Ag / AgCl), and the current density is 87.95 mA / cm at the same voltage 2 .
[0052] Example 3
[0053] The molar ratio of nickel nitrate to copper nitrate is 0.75:0.75. 0.75 Cu 0.75 - Preparation and testing of MOF catalysts:
[0054] The same synthesis method was used as in Example 1, wherein 0.217 g nickel nitrate and 0.180 g copper nitrate were weighed, and other conditions were the same as in Example 1. The final product was named Ni 0.75 Cu 0.75 -MOF.
[0055] After the above catalyst was prepared into a working electrode for electrochemical ammonia oxidation test, see Figure 2 (b), the starting potential is 0.42 (Vvs.Ag / AgCl), and the current density is 78.12 mA / cm at the same voltage 2 .
[0056] Example 4
[0057] The molar ratio of nickel nitrate to copper nitrate is 0.5:1. 0.5 Preparation and testing of Cu1-MOF catalyst:
[0058] The same synthesis method was used as in Example 1, wherein 0.145 g nickel nitrate and 0.241 g copper nitrate were weighed, and other conditions were the same as in Example 1. The final product was named Ni 0.5 Cu1-MOF.
[0059] After the above catalyst was prepared into a working electrode for electrochemical ammonia oxidation test, see Figure 2 (b), the starting potential is 0.42 (Vvs.Ag / AgCl), and the current density is 58.13 mA / cm at the same voltage 2 .
[0060] Example 5
[0061] The molar ratio of nickel nitrate to copper nitrate is 0.25:1.25. 0.25 Cu 1.25 - Preparation and testing of MOF catalysts:
[0062] The same synthesis method was used as in Example 1, wherein 0.072 g of nickel nitrate and 0.301 g of copper nitrate were weighed, and other conditions were the same as in Example 1. The final product was named Ni 0.25 Cu 1.25 -MOF.
[0063] After the above catalyst was prepared into a working electrode for electrochemical ammonia oxidation test, see Figure 2 (b), the starting potential is 0.43 (Vvs.Ag / AgCl), and the current density is 56.48 mA / cm at the same voltage 2 .
[0064] Comparative Example 1
[0065] Preparation and testing of Ni-MOF catalyst with a molar ratio of nickel nitrate to copper nitrate of 1.5:0:
[0066] (1) Weigh 0.435 g nickel nitrate and 0.249 g terephthalic acid, add 32 mL N,N-dimethylformamide, 2 mL anhydrous ethanol, and 2 mL deionized water, and mix thoroughly by ultrasonication.
[0067] (2) The mixed solution was transferred to a polytetrafluoroethylene-lined autoclave and reacted in an oven at 140°C for 10 h.
[0068] (3) After the reaction was completed, the reactor was cooled to room temperature and the obtained precipitate was washed three times by centrifugation with anhydrous ethanol and deionized water respectively.
[0069] (4) Finally, the product was dried in a vacuum oven at 60 °C for 12 h. The obtained green powder was Ni-MOF.
[0070] After the above catalyst was prepared into a working electrode for electrochemical ammonia oxidation test, see Figure 2 (b), the starting potential is 0.61 (Vvs.Ag / AgCl), and the current density is 14.85 mA / cm at the same voltage 2 .
[0071] Comparative Example 2
[0072] Preparation and testing of Cu-MOF catalyst with a molar ratio of nickel nitrate to copper nitrate of 0:1.5:
[0073] (1) Weigh 0.301 g of copper nitrate and 0.249 g of terephthalic acid, add 32 mL of N,N-dimethylformamide, 2 mL of anhydrous ethanol, and 2 mL of deionized water, and mix thoroughly by ultrasonication.
[0074] (2) The mixed solution was transferred to a polytetrafluoroethylene-lined high-pressure reactor and reacted in an oven at 140°C for 10 h.
[0075] (3) After the reaction was completed, the reactor was cooled to room temperature and the obtained precipitate was washed three times by centrifugation with anhydrous ethanol and deionized water respectively.
[0076] (4) Finally, the product was dried in a vacuum oven at 60 °C for 12 h. The obtained blue powder was Cu-MOF.
[0077] After the above catalyst was prepared into a working electrode for electrochemical ammonia oxidation test, see Figure 2 (b), the starting potential is 0.45 (Vvs.Ag / AgCl), and the current density is 28.56 mA / cm at the same voltage 2 .
[0078] Ni1Cu prepared in Example 2 and Comparative Example 1 0.5 XRD patterns of -MOF and Ni-MOF can be found in Figure 1 ,It can be seen that the characteristic diffraction peaks of the sample are basically consistent with the simulated diffraction peaks of the standard card CCDC#985792 of Ni-MOF in the Cambridge Crystal Structure Database, indicating that Ni-MOF was successfully synthesized. Peak splitting was observed in the main peak, indicating that the lattice deformation was caused by the introduction of Cu into the Ni-MOF structure.
[0079] The comparison of the ammonia oxidation reaction and oxygen evolution reaction performance of the Ni-Cu-MOF samples prepared in Examples 1 to 5 and Comparative Examples 1 to 2 is shown in Figure 2 .
[0080] Depend on Figure 2 (a) with Figure 2(c) By comparison, it can be seen that the current density of the same catalyst increases significantly after adding NH4Cl solution, indicating that the Ni-Cu-MOF catalyst has a significant catalytic effect on ammonia oxidation, and with the addition of copper, the current density shows a pattern of first increasing and then decreasing.
[0081] Depend on Figure 2 (b) with Figure 2 (d) By comparison, we can see that, that is, LSV curve comparison, Ni1Cu 0.5 -MOF catalyst has a maximum current density of 87.95 mA / cm 2 , the starting potential is as low as 0.39 (V vs.Ag / AgCl), and the catalytic activity is optimal.
[0082] It was further verified that the incorporation of copper makes the ammonia oxidation reaction more selective and dominant in the competition with the oxygen evolution reaction. Its current density is much greater than that of the oxygen evolution reaction, and its starting potential is lower.
[0083] The double layer capacitance (Cdl) of the Ni-Cu-MOF samples prepared in Examples 1 to 5 and Comparative Examples 1 to 2 in 1M KOH+0.5M NH4Cl electrolyte is shown in FIG. Figure 3 .Ni1Cu 0.5 -MOF has the largest double layer capacitance, which is 1.8mF / cm 2 , has the best electrochemical active specific surface area, and its trend is consistent with the activity curve.
[0084] Example 2 Preparation of Ni1Cu 0.5 - Steady-state test (it) of MOF samples in 1M KOH and 1MKOH+0.5M NH4Cl electrolyte at 0.65 (V vs..Ag / AgCl) voltage. See Figure 4 As can be seen from the figure, the catalyst Ni1Cu 0.5 -MOF oxidation current density reaches equilibrium after an initial drop due to concentration polarization. During the entire test process, the catalyst current density of the electrolyte containing ammonia is much greater than that of the electrolyte without ammonia, and the AOR activity is obvious. Finally, the values are stabilized at 35.18 mA / cm 2 , 7.04mA / cm 2 .
[0085] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A method for preparing a copper-doped Ni-MOF catalyst, characterized in that: include, Copper nitrate, nickel nitrate and terephthalic acid are added into a solvent consisting of N,N-dimethylformamide, anhydrous ethanol and deionized water, and ultrasonically treated to obtain a mixed solution. The mixed solution was transferred to a polytetrafluoroethylene-lined autoclave and heated for reaction; After the reaction is completed, the reactor is cooled to room temperature and taken out. The reactants are centrifuged, washed, and dried to obtain a gray-blue powder, which is the copper-doped Ni-MOF catalyst.
2. The preparation method according to claim 1, characterized in that: The volume ratio of N,N-dimethylformamide, anhydrous ethanol and deionized water is 32:2:2; The molar ratio of terephthalic acid to the total amount of metal ions is 1-1.5 mmol: 1-1.5 mmol; The ratio of the N,N-dimethylformamide to terephthalic acid is 30-32 mL: 1-1.5 mmol.
3. The preparation method according to claim 1 or 2, characterized in that: The molar ratio of the nickel nitrate to the copper nitrate is 0-1.5:0-1.
5.
4. The preparation method according to claim 3, characterized in that: The molar ratio of the nickel nitrate to the copper nitrate is 1:0.
5.
5. The preparation method according to claim 1, characterized in that: The ultrasonic treatment comprises an ultrasonic time of 20 to 30 minutes and an ultrasonic power of 100 to 200W.
6. The preparation method according to claim 1, characterized in that: The heating reaction has a reaction temperature of 140° C. and a reaction time of 10 h.
7. The preparation method according to claim 1, characterized in that: The washing comprises washing the product with anhydrous ethanol and deionized water for 2 to 3 times respectively.
8. The preparation method according to claim 1, characterized in that: The drying includes vacuum drying at a temperature of 60° C. and a drying time of 10 to 12 hours.
9. The copper-doped Ni-MOF catalyst prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the catalyst as claimed in claim 9 in electrochemical ammonia oxidation.
Citation Information
Cited By
Preparation method of bimetallic monatomic catalyst based on electrochemical dynamic regulation and control
CN119742384A